Critical reflections: Experiencing discrimination, disrespect and disregard; forming a professional identity - Madileng, Mary M. (Unisa, 2014)
This article offers a brief account of some critical incidents in the author’s educational journey as a learner and teacher in South African schools and universities, and an analysis of the influence of these incidents on the formation of her professional identity. It examines how social interactions and engagement with peers and students have helped to construct and reconstruct her professional identity, allowing her to better recognise herself as an educator shaped by experiences of various forms of discrimination, disrespect and disregard. These experiences and her critical reflection on them have proved valuable for the development of her personal ‘voice’ as a reflective professional. The author argues that the process of critical reflection has led to a deeper understanding of how negative (and some positive) experiences in her journey from rural primary school learner to university lecturer have been positive for strengthening her determination to succeed academically and to be the kind of teacher in academia who aims to be respectful and supportive of all students.
Keywords: Epistemic injustice -- South African education; Professional identity -- South African higher education; Blacks, disrespect -- South African higher education